2017
DOI: 10.1002/jobm.201600464
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and composition of rhizospheric soil and root endogenous bacteria in Panax notoginseng during continuous cropping practices

Abstract: Rhizobacteria and endophytic bacteria play important roles in protecting host plants from infection by phytopathogens, which cause soil-borne diseases and severely impair plant health. Panax notoginseng is negatively affected by continuous cropping and becomes vulnerable to attack by microbial pathogens. In the present study, culture-independent Illumina MiSeq was used to investigate root-endophytic and rhizospheric bacteria in response to continuous cropping of P. notoginseng. Numbers of rhizospheric bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 33 publications
6
65
1
Order By: Relevance
“…In addition, fallow soils showed relatively higher overall fungal activity, whereas fungal diversity was similar between continuously cropped soil and the S_CK, suggesting that fungal diversity gradually recovers to unplanted control soil with time of fallowing. Severe root-rot disease has long been known as a major problem in continuous cropping (Tan et al, 2017a). Consistently, we detected a relatively higher fungal community diversity in healthy tissues and rhizospheric soils compared to diseased samples.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In addition, fallow soils showed relatively higher overall fungal activity, whereas fungal diversity was similar between continuously cropped soil and the S_CK, suggesting that fungal diversity gradually recovers to unplanted control soil with time of fallowing. Severe root-rot disease has long been known as a major problem in continuous cropping (Tan et al, 2017a). Consistently, we detected a relatively higher fungal community diversity in healthy tissues and rhizospheric soils compared to diseased samples.…”
Section: Discussionsupporting
confidence: 84%
“…Due to limited land access, only one plot was used for each zone. However, we randomly collected 15 soil cores from the plow layer (0-30 cm in depth), thoroughly pooled them as a composite sample and divided the pooled samples into three replicates to make the samples more representative Tan et al, 2017a). Fallow soil zones were left unplanted for the specified number of years after an initial planting and harvesting of A. macrocephala.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al [23] and Wu et al [24] studied the changes in bacterial community structure in the rhizospheric soil of konjac and vanilla after continuous cropping, and found that continuous cropping changed the composition and structure of bacterial communities, resulting in a reduction in bene cial bacteria and an increase in harmful bacteria. Tan et al [25] used high-throughput sequencing to study changes in the diversity and composition of rhizospheric soil microbes and endophytes of Panax notoginseng after three years of continuous cropping, and found that bacteria decreased over time. Further, the bacterial diversity of the rhizospheric soil of healthy Panax notoginseng was greater than that of diseased plants.…”
Section: Introductionmentioning
confidence: 99%